Method of calculation of electromagnetic torque and energy losses of three-phase induction motors when powered by a regulated single-phase voltage - Shurub, Yu. V.; Vasilenkov, V. Ye.; Tsitsyurskiy, Yu. L. (Національний технічний університет "Харківський політехнічний інститут", 2022)
Single-phase power supply of induction motors is used in public utilities, in microclimate control systems for remote agricultural consumers, in water supply and pipeline transport systems, etc. In practice, there is the use of induction motors with three-phase stator winding in the conditions of single-phase power supply. Starting and operating capacitors are used to enable their operation when powered by a single-phase network. Problem. There are many fairly accurate methods for calculating the characteristics of an induction motor in asymmetric, including single-phase, modes of operation, but they are based on differential equations, which does not allow to obtain analytical expressions for preliminary analysis and synthesis of such systems. Goal. The purpose of this article is to develop the analytical method of definition of electromagnetic torque and energy losses of voltage-regulated three-phase induction motors working according to the scheme of single-phase inclusion with the phase-shifting capacitor. Methodology. The method is based on the theory of symmetric components and analysis of replacement schemes of induction machine in motor and generator modes. Results. The analysis of the obtained data shows that at a constant value of the phase-shifting capacitor capacity induction motor working according to the scheme of single-phase inclusion has a minimum of losses at one value of slip at different values of supply voltage. Therefore, if you keep this slip constant when the load changes, you can achieve a mode of minimizing losses at a constant value of the capacity, optimal for this slip. This shows that the thyristor voltage regulator can be used as an energy-saving element under variable load, while the capacitance of the phase-shifting capacitor can remain constant when changing the load in a wide range provided that this slip is stabilized. Originality. The developed method allows to obtain analytical expressions for comparative analysis of electromagnetic torque and energy losses of three-phase induction motors powered by a single-phase network at different values of the capacity of the phase-shifting capacitor, supply voltage for different variants of schemes for including three-phase induction motors in a single-phase network. Practical value. Based on the developed analytical method, the optimal parameters of phase-shifting capacitors and rational schemes for including three-phase induction motors in a single-phase network can be determined.

Розроблено аналітичну методику розрахунку електромагнітного моменту та втрат енергії регульованих за напругою трифазних асинхронних двигунів при живленні від однофазної мережі за схемою з фазозсуваючим конденсатором. В основу методики покладено метод симетричних складових та аналіз схем заміщення асинхронної машини у двигунному та генераторному режимах роботи. На основі цієї методики можуть бути визначені оптимальні параметри фазозсуваючих конденсаторів та вибрані раціональні схеми включення трифазних асинхронних двигунів в однофазну мережу з регульованою напругою. Показано, що регулятор напруги може бути використаний як енергозберігаючий елемент при однофазному живленні трифазних асинхронних двигунів та його застосування дозволяє використовувати постійну ємність фазозсуваючого конденсатора при зміні навантаження у широких межах.
Методика розрахунку електромагнітного моменту та втрат енергії трифазних асинхронних двигунів при живленні регульованою однофазною напругою
Keywords: induction motor; single-phase supply; voltage regulator; method of symmetric components; phase-shifting capacitor; асинхронний двигун; однофазне живлення; регулятор напруги; метод симетричних складових; фазозсуваючий конденсатор